Cultural Heritage: Revealing Mak Yong's Relationship with Pancasila Values - Delova, Afriliandini Bunga (Universitas Tanjungpura, 2025)
The culture in Indonesia is very diverse and never separated from the values of Pancasila because Pancasila is a reference in culture for the Indonesian nation. Mak Yong performing arts are one example of Indonesian culture that originates from Malay. This study aims to examine the history and traditions of Mak Yong performing arts and identify the valuesof Pancasila contained in Mak Yong performing arts. This study was conducted using a qualitative approach with literature studies as a data collection technique. Literature studies are used to collect information and data from previous studies on the history and traditions of Mak Yong performing arts. This study found that the tradition of Mak Yong performing arts is generally played by women as a form of appreciation and respect for women. The Mak Yong performance also found religious, social, and cultural values so that it is closely related to the values contained in Pancasila.